Pengaruh Penggunaan Media Sosial dan E-Wom Terhadap Kepercayaan dan Minat Beli Belanja Online - Suryadiningrat, Yedi; Rahmat, Tantri Yanuar; Anandita, Rina (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Technological developments in the past five years have been very fast and dynamic. This also has an effect on the use of technology that is used by humans to transact, especially on increasing buying interest. The main objective of this study was to examine the effect of electronic word of mouth (e-wom) and the use of social media on the level of trust and consumer buying interest. To achieve this goal, data was collected using a questionnaire through an online survey of 180 respondents aged 29-39 years and its location in Jakarta. The collected data was analyzed using SPSS and Structural Equation Modeling (SEM) lisrel. The results of this study indicate that the use of social media / Social Networking Sites (SNS) can influence the level of trust and interest in buying consumers while information and comments on online stores / online shops have effect on consumer buying interest. Keywords: use of social media, e-wom, level of trust, interest in buying